Impact of Information and Communication Technology on Economic Growth and Population Health in Malaysia - Afroz, Rafia; Muhibbullah, Md.; Morshed, Mohammad Niaz (Korean Distribution Science Association, 2020)
The objectives of this paper is to examine the association between information and communication technology (ICT), economic growth and population health based on health production model in Malaysia using time series data from 1993–2017. life expectancy at birth and infant mortality rates are used as proxy variables to measure the population health. Furthermore, ICT infrastructure are captured by using three proxies namely internet users, mobile cellular subscriptions, and fixed telephone subscriptions.Using the bound testing technique of cointegration, the new critical values of the test are recalculated to fit small sample data based on the response surface suggested by Pearson et al. (2006). This study finds that ICT affects population health significantly and positively in the long- and short-run. This is because ICT inclusion improves human health and longevity. Whereas, economic growth has no significant impact on the population’s health both in the short- and long-run. The findings indicate that a weak global economy affects Malaysia’s economic growth and reduces the health expenditure per capita. The results of this study suggest that policymakers must develop policies that improves public health by increasing health literacy, disseminating health information and facilitating medical facilities. This study also suggests that health care systems should to concentrate on digital inclusion.